Design improvements in underground watering system for small local farming industries - Ariff, Tasnim Firdaus; Tukiman, Nurul Hannah Atikah; Bahar, Rubina (IOP Publishing, 2016)
The implementation of underground watering system is basically to supply crops with enough quantities of water. In Malaysia, most farming industries use sprinkler irrigation system. The water is only distributed over the surface whilst the roots actually need water the most. Thus, this research is conducted to design the improvements of watering system for small local farming industries by using underground watering system. Design improvements of the watering system had been done using CATIA software. The design had been fabricated using rapid prototyping/3D printer, tested and evaluated by conducting experiments. Four different plants were prepared and labelled as Plant A, Plant B, Plant C, and Plant D. Plant A and Plant C were not be equipped with the underground watering device while Plant B and Plant D were equipped with the device. The growth of every plant is measured in terms of height, number of newly grown leaves, number of flowers and number of fruits for the duration of 60 days. The plant equipped with the device has the quickest growth measurement (59.68%), continued to produce new leaves rapidly (89.20%), and produced the most number of flowers (19 flowers) and fruits (15 fruits) when compared with the plants without the underground watering device. The difference in growth development is very significant. Therefore, the underground watering system does have a positive impact in nourishing the plant from the root efficiently and can be used productively in small local farming industries.